Detection of miR-21, MUC1mRNA and VEGF Protein Biomarkers Expression Changes in Oral Squamous Cell Carcinomas (OSCC) in Peripheral Blood - Payehghadr, Shaghayegh; Bahrami, Naghmeh; Mohammadi, Farnoush; Naji, Tahereh; Mohamadnia, Abdolreza (Asian Pacific Journal of Cancer Biology, 2018)
Background and purpose: Oral squamous cell carcinoma is a common type of cancer and one of the most important causes of death in the world; therefore, this study investigates the expression of miR-21, MUC1 mRNA and VEGF protein in peripheral blood for early detection and better treatment of this cancer using Real-Time RT-PCR and Elisa. Materials and methods: In this experimental study, 50 OSCC patients and 50 healthy subjects were selected as controls. The total RNA in peripheral blood was extracted by RNA extraction kit and quality evaluation of extracted RNA was measured by NanoDrop.For the synthesis of cDNA, Viva 2-steps RT-PCR kit was used. Expression of miR-21 and MUC1 mRNA were measured by Real-Time RT-PCR and used Elisa for VEGF protein. The relationship between the expressions of these biomarkers was evaluated with tumor staging and progression of cancer. Results: The average age difference is not significant in these two groups by using t-test. The miR-21 was positive in 43 out of 50 OSCC patients (86%), and it was also 14 out of 50 healthy subjects (28%). The MUC1 mRNA was positive in 35 out of 50 OSCC patients, indicating 70% sensitivity, and it was positive in 9 of the 50 healthy subjects(18%). The serum levels of VEGF protein were measured using Elisa; it was positive in 32 out of 50 OSCC patients (64%) and this biomarker in healthy subjects report was not positive, indicating that the specificity is 100%. Conclusions: Overall, the miR-21, MUC1 mRNA and VEGF protein biomarkers could be suggested as a diagnostic screening test for the early detection of diseases. To prove further research is recommended further studies with a larger sample size to be done.